Does Digital Transformation Enhance Corporate ESG Performance? Evidence from China - Chen, Siru (Transactions on Economics, Business and Management Research, 2024)
Digital transformation has endowed enterprises with new growth momentum, but can it further improve their Environmental (E), Social (S), and Governance (G) performance? Based on data from Chinese A-share listed companies from 2011 to 2021, this paper empirically examines the impact of digital transformation on corporate ESG performance and its underlying mechanisms. The study finds that digital transformation significantly enhances corporate ESG performance. Mechanism analysis reveals that the increase in digitalization levels not only strengthens enterprises’ capabilities for green technological innovation but also reduces internal information asymmetry, both of which contribute to the improvement of corporate ESG practices. Moreover, the paper finds that the positive impact of digital transformation on ESG performance diminishes over time. Therefore, to sustain and enhance ESG performance, companies should consider continuous investment in digital technologies. This study enriches and extends research on the applications of digital transformation, providing valuable insights for driving corporate digital transformation and improving ESG performance.